The Importance of Teaching Techniques, Environment and United Arab Emirates University Assessment for Newly Admitted Undergraduate Students In the United Arab Emirates University - Ksiksi, Taoufik Saleh; Chaudhry, Rabia Hameed (Journal of Research in Educational Sciences, 2012)
Teaching undergraduate students requires innovative teaching methods to enhance students’ learning. A combined approach using various teaching strategies has been reported to be necessary for a positive shift in students’ learning. In the present study, three hypotheses relating to United Arab Emirates University UAEU undergraduate education is assessed for both male and female students. To test these hypotheses, a teaching survey was conducted during the academic year of 2007. The survey targeted undergraduate students during their early years (first to third year students) within the United Arab Emirates University. A total of 33 students were surveyed, sixteen male students and seventeen female students. 58% of the female students strongly agreed with the necessity of using Blackboard in biology courses, while only 31.3% of males had the same opinion. Between 41% and 59% of females and between 50% and 81.3% of males strongly agreed to the usefulness of PowerPoint presentations in learning and understanding course content. Regarding the necessity of the textbook at the course, 41.2% and 25.0% of females and males strongly agreed that the course textbook was important in understanding biology topics. In short, teaching techniques do constitute an important part in the effectiveness of the learning process and this was supported by students and instructors alike. No single technique could be sufficient to deliver a comprehensive learning experience. The use of technology has to play a part in the delivery of the course, especially now that our youngsters are more and more attracted to use technological equipment in their daily lives.